Meningkatkan Kemampuan Menulis Pengalaman Pribadi Melalui Metode Pemodelan Bentuk Teks Kelas VIII di Madrsah Tsanawiyah Negeri 8 Kampar - Efrita, Zeni (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
In this research, it is hoped that the teacher will be able to play his role as a learning innovator. Increasing the teacher's teaching creativity is absolutely developed. This study uses a classroom action research approach to obtain data and analysis through reflective, participatory, and collaborative studies. Program development is based on data and information from students, teachers, and the social setting of the class naturally through two stages of the class action research cycle. To improve students' personal experience writing skills, classroom action research was carried out using the text form modeling method. This research was conducted at MTsN 8 Kampar with two cycles. In the first cycle there were some who had not been able to do the task properly because the teacher had not given clear instructions. In the second cycle, students and teachers have been able to create a conducive learning situation so that student learning activities have increased. Likewise the product results in the form of personal experience writing also experienced an average increase from 75 to 83. In the implementation of cycle one and cycle two it can be concluded that learning with the text form modeling method can increase activity and product results of personal experience writing in class VIII students at MTsN 8 Kampar